ANCESTRAL KNOWLEDGE: AN EPISTEMOLOGICAL WEAVING - Christian Pedroso Martins, Alan (Revista Gênero e Interdisciplinaridade, 2026)
This article focuses on ancestral African and Afro-Brazilian wisdom as a legitimate, urgent, and counter-hegemonic epistemological path, opposing the rationalist and Cartesian logic imposed by colonial Eurocentrism. The central figures in this article, embodying this historical, philosophical, and existential trajectory, are the Black women and the Black elders. These entities, incorporated into the ritual practices of Umbanda and manifested in the terreiros (religious centers) scattered throughout various regions of Brazil, act as guardians of collective memory and oral tradition. In this way, they bring to life the wisdom, strength, and survival strategies developed under the violence of the tragic reality of slavery that, stemming from past centuries, still haunts the present day. Through their ritual and bodily performance, these figures resignify the knowledge accumulated over the centuries, redefining the environment of the slave quarters and captivity from a spiraling temporal dynamic in the contemporary context. It is argued that articulating and analyzing such entities today fractures the epistemic monologue of the West and enables the construction of new conceptual tools, grounded in peripheral experiences and decolonial and anti-racist shifts. The study recovers the relevance of elders and the sacred territory of the terreiro (Afro-Brazilian religious space) as producers of signs, culture, and political agency, demonstrating how these elements profoundly permeate the social, cultural, and affective aspects of the formation of Brazilian society. It concludes that understanding ancestral knowledge and the concept of the crossroads as indispensable methodological frameworks allows for a break with the prevailing epistemicide, accessing a substantially assertive, profound, and complex understanding of human relations and the structures that move the prevailing social fabric.